THE INTERNATIONAL WHEELCHAIR BASKETBALL FEDERATION’S CLASSIFICATION SYSTEM: THE PARTICIPANTS’ PERSPECTIVE (Kinesiology, 2017)
The purpose of this exploratory study was to evaluate opinions of elite athletes, coaches and classifiers regarding the International Wheelchair Basketball Federation’s (IWBF) functional classification system. We were also interested in the athletes’ perspective regarding potential changes to the classification system. In addition, we compared the generalized opinions reported by the athletes to those of coaches and classification officers. This survey was administered during the Wheelchair Basketball Gold Cup (Amsterdam, 2006). Seventy-nine athletes, 50 men and 29 women, as well as 12 coaches and 14 classifiers completed the survey. The first part of the survey addressed demographic characteristics of the participants. The second part focused on their opinions regarding the current classification system. Based on the survey responses, athletes reported that the IWBF classification system is generally satisfactory. However, athletes as well as coaches and classification officers did report some specific concerns about this classification system. These concerns included changes in an athlete classification, athlete cheating and communication between classifiers and athletes. Athletes, coaches and classifiers, as the wheelchair basketball’s primary constituent groups, have a vested interest in the evolution of the game and should be included in the evaluation and modifications to the functional classification system. This study has demonstrated that a classification specific survey could provide useful information and insight into the perspectives of these constituent groups.Key words: survey, disabled sports, athletes, disabilities